The Effect of Vitamin E Administration on Histopathological Description of Mice (Mus musculus) Liver ExposedÂ toÂ Mercuric Chloride - Charisma, Acivrida Mega; Arianing, Intan Febiola (Jurnal Kedokteran Brawijaya, 2020)
Mercuric chloride may deposit in the liver with a high metabolic rate, delivering substrate and energy from one metabolic system to others, and processing and synthesizing various substances transported to the body. This research aimed to determine the effect of vitamin E administration on liver histopathology of mice (Mus musculus) exposed to mercuric chloride and to determine the histopathological image of the liver. Samples were grouped into P0 (not treated), P1 (mercuric chloride 50 mg/kgBW), P2 (mercuric chloride 50mg/kgBW + vitamin E 50mg/kgBW), P3 (mercuric chloride 50mg/kgBW + vitamin E 100mg/kgBW), and P4 (mercuric chloride 50mg/kgBW + vitamin E 150mg/kgBW) using experiment laboratory method. The data were analyzed using the One Way ANOVA to recognize the difference in changes in vitamin E on hepatocytes damage exposed to mercury chloride. The results showed mercury chloride damages hepatocyte, while the administration of vitamin E as a whole showed changes in hepatocyte repair. The optimal dose for hepatocyte repair is 100mg/kgBW.Â